Principle of reasonableness in international standards of civil proceedings - Lichman, Leonid (International journal of law, crime and justice, 2022)
The principle of reasonableness holds a prominent place in the system of principles of any procedural activity. To achieve the goals and objectives of civil proceedings, reasonableness is either present or should be present in the daily routine of a judge in the administration of justice and is expressed in the judge's reasonable procedural actions upon consideration of each particular case. The aim of the study is to highlight the statutory consolidation and reflect the role of the principle of reasonableness within international standards of justice, the legal positions of the European Court of Human Rights (ECHR) and procedural law of some European states. The main method for this study was the weighing method. Also, the study used comparative legal methods. The authors of the study state that a principle and a concept of reasonableness is not and cannot be defined within a rigid framework since reasonableness is an evaluation category that covers its essence and purpose in practice. Moreover, a particular controversial situation, a certain set of circumstances and conditions prevailing in a particular case are decisive.